Assistance for Adolescents in Preventing Stunting During the First 1000 Days of Life through the Formation of 'REDAKZI PENTING' (Health and Nutrition-Aware Adolescents Caring for Stunting) in Tambak Oso Waru Village, Sidoarjo - Ika Mustika; Esti Novi Andyarini; Moch. Irfan Hadi (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Stunting is one of the nutrition problems that is a national priority today. Stunting occurs as a result of a lack of nutritional intake, recurrent infectious diseases and inadequate family factors or psychosocial factors, especially in the first 1000 days of life. Adolescents, as prospective parents, will give birth to the next generation and need to have adequate knowledge about health, nutrition and stunting so that nutritional deficiencies do not occur, especially in the first 1000 days of life. This community service activity aims to improve the knowledge, attitudes and behaviour of adolescents in preventing stunting, especially in the first 1000 days of life, through the formation of the "REDAKZI PENTING" community (Teenagers Aware of Health, Nutrition and Care for Stunting). Activities were carried out in Tambak Oso Village Sidoarjo using the CBR method involving village community stakeholders and Tambak Oso Village Health workers. Teenagers are given reproductive health education, adolescent nutrition, and stunting as a provision for the Redakzi Penting community. The knowledge gained by adolescents in Health Education activities will be conveyed to other communities so that community awareness, especially adolescents, towards health and stunting increases.